Characterization of the major light-harvesting complexes (LHCBM) of the green alga Chlamydomonas reinhardtii. - Alberto Natali; Roberta Croce (PLoS ONE)
Nine genes (LHCBM1-9) encode the major light-harvesting system of Chlamydomonas reinhardtii. Transcriptomic and proteomic analyses have shown that those genes are all expressed albeit in different amounts and some of them only in certain conditions. However, little is known about the properties and specific functions of the individual gene products because they have never been isolated. Here we have purified several complexes from native membranes and/or we have reconstituted them in vitro with pigments extracted from C. reinhardtii. It is shown that LHCBM1 and -M2/7 represent more than half of the LHCBM population in the membrane. LHCBM2/7 forms homotrimers while LHCBM1 seems to be present in heterotrimers. Trimers containing only type I LHCBM (M3/4/6/8/9) were also observed. Despite their different roles, all complexes have very similar properties in terms of pigment content, organization, stability, absorption, fluorescence and excited-state lifetimes. Thus the involvement of LHCBM1 in non-photochemical quenching is suggested to be due to specific interactions with other components of the membrane and not to the inherent quenching properties of the complex. Similarly, the overexpression of LHCBM9 during sulfur deprivation can be explained by its low sulfur content as compared with the other LHCBMs. Considering the highly conserved biochemical and spectroscopic properties, the major difference between the complexes may be in their capacity to interact with other components of the thylakoid membrane.